Genetic Diversity in Sporophytic Apomictic Neotropical Savanna Trees: Insights from Eriotheca and Handroanthus Agamic Complexes - Rafaela Cabral Marinho; Mariana Gonçalves Mendes; Clesnan Mendes-Rodrigues; Ana Maria Bonetti; Eduardo Leite Borba; Paulo Eugênio Oliveira; Diana Salles Sampaio (Diversity)
Apomictic populations, which produce seeds with embryos without proper sexual syngamy, often show low genetic diversity, but eventually, such diversity has been reported to be surprisingly high. We studied here the genetic diversity in agamic complexes of Eriotheca crenulata (comb. n. E. gracilipes), E. pubescens (Malvaceae-Bombacoideae), and Handroanthus ochraceus (Bignoniaceae), tropical tree species from the savannas in Central Brazil. We evaluated the genetic diversity and structure of self-fertile polyploid sporophytic apomicts versus self-sterile diploid or tetraploid sexual populations by using dominant ISSR markers. Genetic diversity was either similar or even higher in apomictic populations of E. crenulata and E. pubescens, but the opposite was observed in some populations of H. ochraceus. Only two individuals of E. pubescens showed identical ISSR profiles, so strict clonality in adult individuals was very rare among the studied trees. The genetic variability was notably higher within populations than among populations of H. ochraceus and very similar among and within populations of Eriotheca species. Ordination, clustering, and Bayesian analyses showed a clear distinction between populations of Eriotheca species with different breeding systems. But for H. ochraceus, a sexual population was actually grouped with the apomictics. As in other studies, eventual sexual and recombination events seem to increase genetic diversity in apomictic populations. This may explain the similar genetic diversity among apomictic and sexual populations in the studied agamic complexes and the virtual absence of strict clonal individuals. The results have evolutionary and ecological consequences for the threatened Neotropical savanna trees.